THE EFFECT OF SYSTEMATIC RISK AND IDIOSYNCRATIC RISK ON INVESTMENT RETURNS WITH ESG DISCLOSURE AS A MODERATING VARIABLE IN INDONESIAN AGRO-INDUSTRIAL COMPANIES - Aprillianto, Bayu; Apriono, Markus; Wahyuni, Nining Ika; Fadah, Isti (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
In the face of complex market dynamics, companies are required to effectively manage investment risks while simultaneously implementing responsible sustainability practices. This study aims to analyze the effects of systematic risk and idiosyncratic risk on investment returns, as well as the moderating role of Environmental, Social, and Governance (ESG) disclosure in the relationship between these two types of risk and investment returns in Indonesian agro-industrial companies. Using a quantitative approach, the results reveal that systematic risk has a significant negative effect on investment returns, while idiosyncratic risk has a significant positive effect. Furthermore, ESG disclosure is found to reduce the negative impact of systematic risk and strengthen the positive impact of idiosyncratic risk on investment returns. These findings indicate that risk management integrated with sustainability strategies is a key factor in enhancing investment performance. Therefore, agro-industrial companies are encouraged to improve the quality and transparency of ESG disclosures as part of their risk mitigation strategies and efforts to create long-term value for investors.